Proceedings of the Working Conference on Advanced Visual Interfaces 2004
DOI: 10.1145/989863.989918
|View full text |Cite
|
Sign up to set email alerts
|

How users interact with biodiversity information using TaxonTree

Abstract: Biodiversity databases have recently become widely available to the public and to other researchers. To retrieve information from these resources, users must understand the underlying data schemas even though they often are not content experts. Many other domains share this problem.We developed an interface, TaxonTree, to visualize the taxonomic hierarchy of animal names. We applied integrated searching and browsing so that users need not have complete knowledge either of appropriate keywords or the organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…The taxa for living beings are distributed in a Linnaean classification, where groupings receive a rank, such as Kingdom, Phylum, Class, Order, Family, Genus, and Species (in decreasing order of inclusiveness) [9]. The taxon's attributes are inherited by its children nodes, which in turn can have other attributes that are inherited by their children, and so on.…”
Section: A Taxonomy Treementioning
confidence: 99%
See 1 more Smart Citation
“…The taxa for living beings are distributed in a Linnaean classification, where groupings receive a rank, such as Kingdom, Phylum, Class, Order, Family, Genus, and Species (in decreasing order of inclusiveness) [9]. The taxon's attributes are inherited by its children nodes, which in turn can have other attributes that are inherited by their children, and so on.…”
Section: A Taxonomy Treementioning
confidence: 99%
“…The database structure is based on the taxonomic tree, which ranks each node based on the Linnaean classification: Kingdom, Phylum, Class, Order, Family, Genus, and Species, in decreasing order of inclusiveness [9]. Each collected specimen is recorded in the database as children of its species node, which is children of a higher rank and so on, forming the taxonomic hierarchy.…”
Section: A Data Modelmentioning
confidence: 99%
“…Such taxonomies are composed of taxonomic units known as taxa (singular: taxon), frequently arranged in a hierarchical structure and related to one another by 'parent-child' relationships, as can be seen in Figure 2.1. These taxa are distributed in a Linnaean classification, where groupings receive a rank, such as Kingdom, Phylum, Class, Order, Family, Genus, and Species (in decreasing order of inclusiveness) (LEE et al, 2004). The taxon's attributes are inherited by its children nodes.…”
Section: Taxonomy Treementioning
confidence: 99%
“…Our previous work on SpaceTree and TaxonTree suggested that interaction with and interpretation of node-link tree structures pose little difficulty for novice users and therefore interactive tree visualizations can be used for a broad audience [27], [32].…”
Section: Take Advantage Of Human Perception Of Treesmentioning
confidence: 99%